Driving technological innovation through intellectual capital: Industrial revolution in the transportation sector - Svetlana Vasilievna Zemlyak; Ludmila Timofeevna Kiyashchenko; Elena Victorovna Ganicheva (Economies, 2022)
The purpose of this research is to investigate intellectual capital as a driver of technological innovation considering the industrial revolution in Russia's transportation sector. The study was driven by the recent technological advancements in Russia's transportation industry and the huge economic importance of the sector to the economy, showing the need to understand the progress achieved in the sector. The study was carried out using primary data collected from respondents in managerial positions in firms operating in the transportation sector. A total of 455 respondents were used, and data were collected using a structured closed-ended questionnaire. The fields of intellectual capital considered were structural, social, human, and relational capital. The model was evaluated using CFA, reliability, and validity tests, while the study hypotheses were tested using SEM. The results reveal that structural capital, social capital, human capital, and relational capital have a significant and positive influence on technological innovation in Russia's transportation sector. Human and social capital was found to have the largest effect. The study recommends that, for firms to implement technological innovation, they should consider human capital, such as specialized knowledge, skills, expertise, experiences, and abilities embedded within organizations personnel, and social capital, such as effective communication, the laid down mechanisms of coordination and communications within the organization, human ties, trust, and relationships. They should also improve their absorptive technology capacity.
Keywords: 330; human capital; intellectual capital; relational capital; social capital; structural capital; technological innovation